2023
DOI: 10.1097/hc9.0000000000000013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of statins and aspirin on HCC risk in alcohol-related cirrhosis: nationwide emulated trials

Abstract: Background and Aims: Observational studies have shown an association between statin or aspirin use and a decreased risk of HCC, but the effects of a well-defined treatment strategy remain unknown. We emulated trials of the effects of continuous statin or aspirin use on HCC risk in patients with cirrhosis due to alcohol-related liver disease (ALD cirrhosis). Approach and Results: We specified target trials for statins and, separately, aspirin and emulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…A total of 20 studies were excluded due to overlapping study populations (eight in South Korea, seven in Taiwan, two in the USA, two in Hong Kong, one in Sweden), and the details of these are outlined in Table 1 . There was finally a total of sixteen studies, twelve cohort [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] and four case-control [ 46 , 47 , 48 , 49 ], selected for inclusion. The overall search and study selection process is summarised in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 20 studies were excluded due to overlapping study populations (eight in South Korea, seven in Taiwan, two in the USA, two in Hong Kong, one in Sweden), and the details of these are outlined in Table 1 . There was finally a total of sixteen studies, twelve cohort [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] and four case-control [ 46 , 47 , 48 , 49 ], selected for inclusion. The overall search and study selection process is summarised in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of five cohort studies reported on patients with a diagnosis of cirrhosis specifically, involving a large number of patients (n = 122,645). Two studies [ 37 , 39 ] (n = 6768) performed a subgroup analysis for patients with hepatitis B-related cirrhosis, while the other three [ 34 , 38 , 44 ] (n = 115,877) wholly comprised patients with cirrhosis. One study encompassed the breadth of the aetiology of cirrhosis [ 44 ], one focused on patients with only alcohol-related cirrhosis [ 38 ], and the final study involved patients with solely HBV- and HCV-related cirrhosis [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First is the lack of accounting for the use of medications. Multiple cohort studies have suggested that both metformin and statins are associated with reduced risks of cirrhosis and HCC, 9 yet the VA study did not account for metformin use, and the UK Biobank study did not account for either. Other time-varying co-variates that can impact the development of cirrhosis and HCC (changes in body mass index, alcohol consumption etc.)…”
mentioning
confidence: 99%